1998
DOI: 10.1038/bjc.1998.419
|View full text |Cite
|
Sign up to set email alerts
|

Assessing patients' needs and preferences in the management of advanced colorectal cancer

Abstract: Summary Clinical decision-making in advanced cancer is a highly complex process. Many factors are thought to influence this processarguably the most important of these is the patient's own preference. Studies show that most patients want to be fully informed as to their diagnosis and involved in clinical decision-making. However, the attitudes of healthcare workers often preclude patient involvement. Studies have also shown that acceptability of chemotherapy for minimal therapeutic gain differs markedly betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…2002), who have shown that chemotherapy causes short-and long-term side-effects that can provoke distress and even affect patients' quality of life. In addition, as in other studies (Redmond 1998;Batchelor 2001;Jacobsen et al . 2002), the nurses unanimously stated that patients receiving chemotherapy have psychological needs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2002), who have shown that chemotherapy causes short-and long-term side-effects that can provoke distress and even affect patients' quality of life. In addition, as in other studies (Redmond 1998;Batchelor 2001;Jacobsen et al . 2002), the nurses unanimously stated that patients receiving chemotherapy have psychological needs.…”
Section: Discussionsupporting
confidence: 81%
“…1995; Seymour et al . 1997; Redmond 1998; Sitzia & Wood 1998b; Del Mastro et al . 2002; Jacobsen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The trend with age and the lower rate of treatment in single persons may, however, reflect patient choice as recent studies show that it is younger patients and those with families who are more willing to accept chemotherapy for a limited clinical benefit. 19 Indeed, it is important to underline that the results reported in this paper represent a time when the clinical benefits of chemotherapy, although promising, were not yet fully established. The strong eVects of hospital of first admission are likely to be proxy measures of consultant eVects that reflect their own knowledge, experience and belief in the benefits proVered by chemotherapy, and it is to be expected that these eVects should decrease now that guidelines have been issued.…”
Section: Discussionmentioning
confidence: 90%
“…There is an increasing appreciation of the importance of the palliative effects of treatment in patients with advanced cancer; Redmond (1998) and Minsky (1998) have shown how the overall effectiveness of treatment can be enhanced by using therapies that combine increased well-being for patients with clinical efficacy in terms of objective response and survival. In the present phase III clinical trials, clinically significant palliative benefits were obtained to a similar extent with raltitrexed and 5-FU + LV in terms of weight gain, improvements in performance status and reductions in disease symptoms (e.g.…”
Section: Objective Response Ratesmentioning
confidence: 99%